Afferent cardiac signals modulate attentional engagement to low spatial frequency fearful faces. (July 2018) - Azevedo, Ruben T.; Badoud, Deborah; Tsakiris, Manos
Abstract: Despite the growing consensus that the continuous dynamic cortical representations of internal bodily states shape the subjective experience of emotions, physiological arousal is typically considered only a consequence and rarely a determinant of the emotional experience. Recent experimental approaches study how afferent autonomic signals from the heart modulate the processing of sensory information by focussing on the phasic properties of arterial baroreceptor firing that is active during cardiac systole and quiescent during cardiac diastole. For example, baroreceptor activation has been shown to enhance the processing of threat-signalling stimuli. Here, we investigate the role of cardiac afferent signals in the rapid engagement and disengagement of attention to fear stimuli. In an adapted version of the emotional attentional cueing paradigm, we timed the presentation of cues, either fearful or neutral faces, to coincide with the different phases of the cardiac cycle. Moreover, we presented cues with different spatial frequency ranges to investigate how these interoceptive signals influence the processing of visual information. Results revealed a selective enhancement of attentional engagement to low spatial frequency fearful faces presented during cardiac systole relative to diastole. No cardiac cycle effects were observed to high spatial frequency nor broad spatial frequency cues. These findings expand our mechanistic understanding of how body–brain interactions may impact the visual processing of fearful stimuli and contribute to the increased attentional capture of threat signals.